A mutational hotspot in TUBB2A associated with impaired heterodimer formation and severe brain developmental disorders - Di Pasquale, Gabriele; Colella, Jacopo; Di Cataldo, Carola P.; Soler, Miguel A.; Fortuna, Sara; Mizrahi-Powell, Emma; Nizon, Mathilde; Cognè, Benjamin; Turchetti, Valentina; Mangano, Giuseppe D.; Comisi, Francesco F.; Cecchetti, Corrado; et al. (Frontiers in Cellular Neuroscience, 2025)
IntroductionMicrotubules are essential components of the neuronal cytoskeleton. The α- and β-tubulins, variably expressed in the central nervous system, play key roles in neurogenesis and brain development. Pathogenic variants in TUBB2A have recently been identified as an ultra-rare cause of pediatric neurodevelopmental disorders (NDDs). However, the neurological and behavioral manifestations, genotype–phenotype correlations, and underlying disease mechanisms remain poorly understood due to the limited number of reported families.MethodsWe describe a cohort of families presenting with microcephaly, global developmental delay, speech impairment, seizures and/or EEG abnormalities, movement disorders and severe behavioral disorders. Clinical assessments and brain imaging studies were conducted over a 10-year follow-up period. Genetic analysis was performed via whole-exome sequencing (WES), and structural modeling was used to investigate the functional impact of the identified variants.ResultsWES revealed a novel recurrent heterozygous pathogenic variant in TUBB2A (NM_001069.3:c.1172G > A; NP_001060.1:p.Arg391His), identified as the cause of disease in multiple affected individuals from unrelated families. Comparative analysis with previously reported TUBB2A de novo variants confirmed that this novel recurrent mutation affects a highly conserved Arg391 residue within the longitudinal E-site heterodimer interface. Computational modeling demonstrated that the variant disrupts α/β-tubulin heterodimer formation, impairing binding stability at this critical interaction site.DiscussionOur findings expand the phenotypic and genotypic spectrum of TUBB2A-related disorders and identify Arg391 as a mutational hotspot linked to severe brain developmental disorders due to aberrant tubulin dynamics, highlighting the disruption of the α/β-tubulin heterodimer formation as the disease mechanism associated to this novel hotspot variant. These results provide new insights into disease mechanisms and offer a foundation for potential future therapeutic approaches aimed at stabilizing α/β-tubulin interactions.